Survey risk factors in pregnant women who suffer from hydatidiform mole and its clinical course in Alzahra hospital in Rasht from 2003-2007 - Tahere Ziaie; Homa Khanjani; Mohammad Ali Yazdani (Journal of Holistic Nursing and Midwifery)
Introduction: Hydatidform mole is one of the branches of trophoblastic diseases in pregnancy. Trophoblastic diseas in pregnancy is referred to special group of diseases with different invasive and metastasis types. In attention to the importance of this disease and its high incidence in Asian and African countries and scant information in Iran, especially in Guilan, this study aims to determine the risk factors and clinical course in pregnant women who suffer from hydatidiform mole in Alzahra hospital in Rasht from 2003-2007.